The end of romance - Meyer, Lily (Viking, 2026)
After escaping an emotionally abusive marriage, Sylvie Broder heads to graduate school and forms a bold new belief: women will only find true happiness once they abandon romance altogether. Determined to keep love out of her life, she embraces casual relationships and focuses on pleasure without commitment. But when she meets two very different men-kind, steady Robbie and passionate, unpredictable Abie-Sylvie finds her carefully crafted philosophy put to the test, forcing her to rethink what love, freedom, and happiness really mean.